Assessing Theory of Mind by Humor: The Humor Comprehension and Appreciation Test (ToM-HCAT) - Aykan, Simge; Nalçacı, Erhan (Frontiers in Psychology, 2018)
Theory of Mind (ToM) may be defined as the ability to understand the mental states, such as beliefs, desires, intentions, and emotions, of others. Impairment of ToM ability leads to disorders with pathologies in social skills, such as autism spectrum disorder and schizophrenia. In addition to differences in ToM ability among patient populations, there is variation between neurotypical individuals. Unfortunately, ToM tasks are usually developed for children or patients with cognitive disorders and cannot detect variations in healthy adults. As an alternative tool, humor may be used. Humor plays a role in social communication and requires many different cognitive functions. Humor is believed to represent complex high-order cognitive processes. There are numerous types of humor; the most complex type is considered ToM humor, where an understanding of social/emotional content is necessary. Given the need for a ToM assessment test suitable for healthy adult populations, we developed a test for measuring humor comprehension and appreciation, with and without ToM content (ToM-HCAT). The present ToM-HCAT test is a performance test consisting of cartoons. The test measures perceived funniness, reaction time to perceived funniness decision, and meaning inference. Cartoons were selected after pilot studies involving 44 participants. Subscales were constituted according to expert views and confirmed by confirmatory factor analysis (N = 135). Goodness of fit values for the final 35-item test were acceptable to excellent: GFI = .973; AGFI = .970; NFI = .968; RFI = .966, and SRMR = .0665. Both categories were internally consistent (α1 = .842, α2 = .940). External validity was assessed against autistic traits. One hundred and three participants completed the Autism Spectrum Quotient and were grouped by + 0.5 standard deviations from the mean as high in autistic traits. The meaning-inference scores of the subscale with the ToM cartoons were significantly lower (p = .034) for the high autistic traits group, providing evidence of external validity. In conclusion, we developed and validated a test for assessment of ToM by humor comprehension and appreciation. We believe that the present test will be useful for the detection of variations in ToM ability in the healthy adult population.